Os jovens e a leitura: descobertas feitas em uma turma de terceiro ano do Ensino Médio de uma escola pública do interior do estado - Frigo, Clícia (2016)
Many were the discussions involving the reading formation in Brazil over time, and especially reading as a necessary competence to young people in the process of building basic knowledge and training of a reader identity for their inclusion in the Literate world. However, reading is not properly grounded and loss-making skills readings, and generally, come from the fragile country's educational process. Thus, this work – The youths and the reading: findings in a third grade of a public high school in a country town - implies a theorization based on the evolution of reading to date and aims to analyze the reading habits of the students of the third year of high school at Frederico Benvegnú State High School, located in São Domingos do Sul, Rio Grande do Sul. In view of this, this research proposed to investigate the readings, literary or nonliterary, young people are performing, their purpose, and which platform they use to perform these readings. The research consisted of bibliographic and field studies, exploratory in nature. Two questionnaires were applied to students of the third year of high school. The first one sought to know the reading habits of students and to profile reader students and non-readers, selecting only the readers for the second stage of the research. The second questionnaire sought to investigate the behavior of these students, which readings they are performing, their purpose and through which platform they perform, always striving in search of answers to the current situation of reading among young people. Based on the responses of the subjects studied, it was possible to identify the reading experiences that affected these youths, who were the main instigators and reading mediators, just as observing the reading habits of these young people at the present time. The analysis and interpretation of data took place in the light of theoretical as Michèle Petit, Regina Zilberman, Ezequiel Theodoro da Silva, Maria da Glória Bordini and Marisa Lajolo.